2019
DOI: 10.1155/2019/4396108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Acute Kidney Injury among Malaria Patients in Dar es Salaam: A Cross-Sectional Study

Abstract: Introduction. Falciparum malaria still remains as a major cause of morbidity and mortality worldwide. Acute kidney injury is a known complication of malaria, and it is reported to occur in up to 40% of adult patients with severe falciparum malaria in endemic regions like sub-Saharan Africa. Objectives. To determine the prevalence and factors associated with acute kidney injury among falciparum malaria patients in a tertiary level private hospital in Dar es Salaam. Methodology. In a cross-sectional study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Prior to the use of the KDIGO consensus guidelines, the prevalence of AKI in malaria had been significantly underrepresented in both adults and children (7,8). Recent studies using the KDIGO classification, have reported that the prevalence of AKI ranges from 20% to 40% among adults and children with SM, while some studies have reported an AKI incidence of as high as 59% for children (9)(10)(11)(12)(13)(14). Despite the similar frequency of AKI between child and adult SM patients, the overall burden of malaria-associated AKI cases is likely to be greater in children, since the vast majority of SM patients in endemic countries are children (15).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the use of the KDIGO consensus guidelines, the prevalence of AKI in malaria had been significantly underrepresented in both adults and children (7,8). Recent studies using the KDIGO classification, have reported that the prevalence of AKI ranges from 20% to 40% among adults and children with SM, while some studies have reported an AKI incidence of as high as 59% for children (9)(10)(11)(12)(13)(14). Despite the similar frequency of AKI between child and adult SM patients, the overall burden of malaria-associated AKI cases is likely to be greater in children, since the vast majority of SM patients in endemic countries are children (15).…”
Section: Introductionmentioning
confidence: 99%
“…The Kidney Disease: Improving Global Outcomes (KDIGO) defines AKI as the rapid deterioration of renal function, characterised by either: 1) a reduction in urine output to < 0.5 mL/kg/h for 6 hours, 2) an increase in serum creatinine by at least 0.3 mg/dL (26.53 µmol/L) within 48 hours, or 3) an increase in serum creatinine to at least 1.5 times the baseline within 7 days. Using the KDIGO criteria, recent studies have estimated a high prevalence of AKI in patients with malaria of 20% to 40% in adults and up to 59% in children [8,9]. In this case report, the patient met the first two definitions of AKI.…”
Section: Discussionmentioning
confidence: 75%
“…Although not available in all low-resource settings, serum creatinine laboratory values are the most commonly used tools to identify AKI. 1,35,[38][39][40][41][42][43][44][45][46][47][48][49][50] A 2015 multinational cross-sectional study showed that the diagnosis of AKI was made with serum creatinine values alone in 63% of participating facilities, followed by serum creatinine along with urine output in 28% of participating facilities in LMICs. 1 A 2018 qualitative study surveying AKI identification and management practices among 160 intensivists based in provincial and regional hospitals in Thailand showed that the KDIGO criteria for AKI were most commonly used (37%), followed by the AKIN (27.7%) and RIFLE (26.1%) criteria, respectively.…”
Section: Questionsmentioning
confidence: 99%